Desinformação e competência em informação: discussões e possibilidades na Arquivologia - MOURA, Ana Roberta Pinheiro (2021)
The present research had the objective of mapping the possible intersections between the Disinformation phenomenon and the Information Literacy theme in the field of study of contemporary national Archival Science. The study was developed through the Systematic Bibliographic Review in the Reference Database of Periodical Articles in Information Science. The results identified a low academic-scientific production, relating Information Literacy to Archival Science and in what refers to the Disinformation phenomenon, no occurrence was identified in the archival productions, however, it is evident the relation between Information Literacy and Disinformation in Information Science. The result of this work can contribute significantly to both the Archival Science and Information Science as well as to society in general, considering that the Disinformation phenomenon is still poorly understood and comes in a general way devastating society. The results obtained were relevant to confirm that the precepts of the Information Literacy are configured as a possibility of both combat and reduction of Disinformation in society.